SEQUENCE SIMILARITY BETWEEN THE MAMMALIAN BMI-1 PROTOONCOGENE AND THE DROSOPHILA REGULATORY GENES PSC AND SU(Z)2 - van Lohuizen, M; Frasch, Manfred; Wientjens, E; Berns, A (Nature, 1991)
THE bmi-1 proto-oncogene can be activated by Moloney murine leukaemia proviral insertions in E-mu-myc transgenic mice 1,2. It encodes a highly conserved nuclear protein of 324 amino acids which belongs to a family of proteins containing a putative new zinc-finger. Another closely related member of this family is the mouse protein Mel-18 (ref. 3). Here we report on the cloning and characterization of a homologous gene (D-bmi) from Drosophila melanogaster. Our analysis indicates that distinct domains of the mouse Bmi-1 protein, including the putative zinc-finger motif, are highly conserved within the much larger D-Bmi protein. Chromosomal localization and sequence comparison reveal that D-bmi is identical to Posterior Sex Combs (Psc) 4-6 and indicate that the conserved domains between mouse bmi and Psc are also conserved within Suppressor-2 of Zeste (Su(z)2) 6-8.